Preparation method of ferrous fumarate and EDTA iron sodium complex iron agent

CN122998073APending Publication Date: 2026-10-30天富(江苏)科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611477074.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明旨在提供一种富马酸亚铁与EDTA铁钠复合铁剂制备方法,以解决两种铁源在直接混合或湿法制粒过程中容易发生富马酸亚铁氧化、乙二胺四乙酸铁钠迁移、局部游离铁浓度升高、色泽变化以及单位剂量含铁量不均的问题

Benefits of technology

1、通过先形成富马酸亚铁核、再于表干切换点后固定乙二胺四乙酸铁钠,可缩短乙二胺四乙酸铁钠处于可迁移湿相中的时间,并降低富马酸亚铁的湿相氧化风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998073A_ABST
    Figure CN122998073A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a ferrous fumarate and EDTA iron sodium compound iron agent, and belongs to the field of iron nutrition fortification agent preparation. In order to solve the problems of oxidation, migration, color change and uneven iron content per unit dose caused by different iron valence states, coordination structures, dissolution characteristics and particle properties of two iron sources, the application realizes the technical effects of improving storage stability, dissolution consistency and batch reproducibility by means of low-oxygen segmented nucleation, post-lagging after surface drying switching, spectral proportion feedback and low-temperature and low-oxygen double-end-point drying, so that the two iron sources enter the same compound particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of iron fortification preparation, and more particularly to a method for preparing a composite iron preparation of ferrous fumarate and EDTA iron sodium. Background Technology

[0002] Ferrous fumarate has a high ferrous content, while sodium ferric ethylenediaminetetraacetate has a stable coordination structure. The combination of these two can be used to provide iron sources in different forms. However, the two iron sources differ in valence state, coordination state, dissolution behavior, and particle surface properties, making it difficult to guarantee a stable ratio per unit dosage through conventional direct mixing.

[0003] When using wet granulation, ferrous fumarate is prone to oxidation in localized environments with moisture, oxygen, and elevated temperatures. If sodium ferric ethylenediaminetetraacetate enters the wet phase too early, it may migrate with the liquid film and cause a local increase in the concentration of free iron. Material migration can also cause differences in color and dissolution. Relying solely on granulation time or a single moisture value for control is insufficient to simultaneously maintain valence state, achieve uniform proportions, and ensure batch-to-batch reproducibility.

[0004] Therefore, there is a need for a method to prepare a composite iron agent of ferrous fumarate and EDTA iron sodium that can overcome the shortcomings of the existing technology. Summary of the Invention

[0005] This invention aims to provide a method for preparing a composite iron agent of ferrous fumarate and EDTA iron sodium, to solve the problems that easily occur during direct mixing or wet granulation of the two iron sources, such as oxidation of ferrous fumarate, migration of EDTA iron sodium, local increase in free iron concentration, color change, and uneven iron content per unit dose. This invention determines the amount of the two iron sources to be fed according to the target element iron ratio, prepares EDTA iron sodium as a post-dry powder premix, first forms ferrous fumarate cores under low oxygen conditions, and performs post-lamination when the continuous liquid film on the surface disappears but residual adhesion remains. Granulation and lamination are controlled by feedback of the wet phase oxygen exposure index and the ratio of the spectral characteristics of the two iron sources. The drying and release endpoints are then determined by the drying weight loss, water activity, and ferrous ferrous retention rate.

[0006] This invention provides a method for preparing a composite iron agent of ferrous fumarate and EDTA iron sodium, comprising: S1, determining the feeding amounts of ferrous fumarate and EDTA iron sodium according to the target element iron ratio, mixing EDTA iron sodium with a first carrier to obtain a post-dry powder premix, and using ferrous fumarate and a second carrier as pre-feeding components; S2, after inerting in a granulation device, using a deoxygenating adhesive to perform segmented spray granulation on the pre-feeding components to obtain a ferrous fumarate core; S3, determining the surface-dry switching point where the continuous liquid film on the surface of the ferrous fumarate core disappears but still has residual adhesion; S4, adding the post-dry powder premix after the surface-dry switching point, and using a deoxygenating adhesive for pulse spraying and mixing, so that EDTA iron sodium is fixed on the outer layer of the ferrous fumarate core, obtaining composite particles with the two iron sources located in the same particle; S5, drying the composite particles within preset drying temperature and drying oxygen limits to obtain the finished composite iron agent.

[0007] Optionally, S1 includes: determining the elemental iron content of ferrous fumarate and sodium iron ethylenediaminetetraacetate raw materials respectively, and correcting the theoretical feed mass with their respective elemental iron contents; The first carrier is selected from at least one of microcrystalline cellulose, pregelatinized starch, maltodextrin and mannitol, and the relative standard deviation of the sodium iron ethylenediaminetetraacetate content of the post-dry powder premix, as measured by multi-point sampling, is within the premix uniformity limit. The target element iron ratio and premixing uniformity limits are determined by the product formulation and process validation results.

[0008] Optionally, S2 includes: preparing the deoxygenated adhesive with deoxygenated water and maintaining inert gas protection in the preparation, delivery and spraying paths; According to the fixed solid-liquid mass ratio determined through process verification, a representative sample of the pre-feeding component is mixed with a specified amount of water to form a dispersion. The pH of the dispersion is measured at a fixed measurement temperature and a fixed settling time. Based on the measured pH, the amount of microenvironment pH adjusting component is determined. The microenvironment pH adjusting component is added to the pre-feeding component so that the measured pH of the pre-feeding component after adding the microenvironment pH adjusting component enters the stable range determined by the ferrous fumarate retention rate test. The granulation equipment is inertized until the oxygen volume fraction is within the preset oxygen limit, and the particle temperature is maintained within the preset granulation temperature limit during the segmented liquid spraying granulation process. The preset oxygen limit and preset granulation temperature limit are determined by the boundaries of the ferrous iron retention rate satisfying the corresponding release limit in the oxygen volume fraction gradient test and the particle temperature gradient test, respectively. Furthermore, the wet phase oxygen exposure index is obtained, which includes: establishing a correspondence between near-infrared moisture signals and liquid film states using calibration particles with and without continuous liquid films on their surfaces, and determining the boundary value between the two liquid film states as the critical value of the continuous liquid film. The measured oxygen volume fraction before the pre-feeding components are added after inerting by the granulation equipment is used as the inerting reference value, and the inerting reference value is within the preset oxygen limit value; Synchronous data sets of oxygen volume fraction, near-infrared particle moisture and particle temperature are formed according to the sampling time interval. When the near-infrared particle moisture is within the critical value of the continuous liquid film, the wet phase oxygen exposure contribution of the corresponding sampling time interval is recorded as zero. When the near-infrared particle moisture exceeds the critical value of the continuous liquid film, the wet phase oxygen exposure contribution is determined according to the deviation of oxygen volume fraction from the inertization reference value, the oxidation rate correction coefficient corresponding to particle temperature and the sampling time interval, and the wet phase oxygen exposure contribution is accumulated. Furthermore, a first interlocking threshold, a second interlocking threshold, and a preset exposure limit are set, and the first interlocking threshold, the second interlocking threshold, and the preset exposure limit are set in a sequentially increasing relationship. When the wet phase oxygen exposure index reaches the first interlocking threshold, the spray duty cycle of the deoxygenated adhesive is reduced and the inert gas replacement flow rate is increased. When the wet phase oxygen exposure index reaches the second interlock threshold, the spraying is stopped and mixing and inerting are maintained to prevent the cumulative value of the wet phase oxygen exposure index from falling back until the oxygen volume fraction in the equipment is within the reset oxygen limit and the near-infrared particle moisture is within the critical value of the continuous liquid film. Then the surface dry switching determination in step S3 is resumed. When the wet phase oxygen exposure index reaches the preset exposure limit, the corresponding batch will be transferred to isolation status; The first interlock threshold, the second interlock threshold, the reset oxygen limit, and the preset exposure limit are determined by the batch verification relationship between the wet phase oxygen exposure index and the ferrous iron retention rate. The reset oxygen limit is within the preset oxygen limit, and the ferrous iron retention rate corresponding to the second interlock threshold meets the ferrous iron retention rate release limit.

[0009] Optionally, S3 includes: using particle surface imaging to determine the calibration time when the continuous liquid film on the surface disappears, using the adhesion ratio of standard probe powder after a specified mixing time to determine the calibration period when the residual adhesion is qualified, and associating the calibration time and calibration period with the change trajectory of at least one of near-infrared particle moisture, torque and power and exhaust absolute moisture content to establish a surface dryness determination interval with an entry boundary and an exit boundary. When the near-infrared particulate moisture enters the surface drying determination range, the rate of change of torque or power enters the stable zone, and the absolute moisture content of the exhaust air no longer increases within the determination time window, the surface drying switching point is determined to have been reached. When the near-infrared particle moisture has not yet reached the entry boundary along the moisture descent direction, mixing and inertization are maintained. When the near-infrared particle moisture crosses the exit boundary or when the criteria are not simultaneously met by the time the preset waiting period expires, subsequent layering is stopped and the corresponding batch is transferred to the isolation state. Batches that meet the verified rework conditions are reworked according to the safety threshold of low oxygen and ferrous iron retention rate.

[0010] Optionally, S4 includes: acquiring the spectra of the ferrous fumarate standard sample and the sodium ferric ethylenediaminetetraacetate standard sample respectively, and determining the first characteristic band of the response to fumarate and the second characteristic band of the response to the coordination structure of ethylenediaminetetraacetate. After scattering correction and baseline correction of the spectrum of the composite particles, the spectral feature scores are obtained based on the response values ​​of the first and second characteristic bands, respectively. The ratio of the spectral feature scores is determined by using the spectral feature score corresponding to the second feature band as the numerator and the spectral feature score corresponding to the first feature band as the denominator. The elemental iron ratio is determined by using the elemental iron content from sodium iron ethylenediaminetetraacetate as the numerator and the elemental iron content from ferrous fumarate as the denominator. Based on calibration particles with known iron ratios of two iron source elements, a correspondence is established between the ratio of spectral feature scores and the elemental iron ratio. The moving mean and relative standard deviation of the ratio of spectral feature scores are calculated within a continuously moving window. The allowable interval corresponding to the target elemental iron ratio is taken as the target ratio interval, and the maximum allowable relative standard deviation for unit dose iron content uniformity verification is taken as the spatial uniformity limit. Furthermore, during the fixation process of sodium iron ethylenediaminetetraacetate, the moving mean and relative standard deviation are updated according to a continuously moving window. When the moving average is less than the lower limit of the target ratio range, increase the feed rate of the post-dry powder premix per unit time; when the moving average is greater than the upper limit of the target ratio range or the moving average is within the target ratio range, stop feeding. When the relative standard deviation is greater than the spatial uniformity limit, while maintaining the feeding state determined by the moving average, the mixing time is extended and the amount of liquid injected in a single pulse is reduced. The fixation process of sodium ferric ethylenediaminetetraacetate ends only after the moving mean and relative standard deviation of multiple consecutive moving windows are both qualified. The number of consecutive moving windows is determined by the lower boundary of the number of windows whose misjudgment probability does not exceed the preset misjudgment limit in the process verification. Divide the amount of sodium ferric ethylenediaminetetraacetate (EDTA) determined in step S1 by the measured mass fraction of EDTA in the subsequent dry powder premix, and combine it with the allowable deviation determined by process verification to obtain the total feed limit of the subsequent dry powder premix. When the cumulative feeding amount reaches the total feeding limit or the preset control time limit expires and the moving average or relative standard deviation is still unqualified, feeding and spraying are stopped and the corresponding batch is transferred to the isolation state. Batches that meet the verified rework conditions are reworked according to the target element iron ratio, drying loss and ferrous iron retention rate safety threshold.

[0011] Optionally, S5 includes: simultaneously acquiring the loss on drying and water activity during the drying process, taking the loss on drying and water activity reaching their respective release limits as two physical endpoints, and continuing drying when either physical endpoint fails to reach its corresponding release limit; After both physical endpoints reach the corresponding release limits, the near-line ferrous content of the particle sample is determined, and the ferrous retention rate is determined by the ratio of the near-line ferrous content to the ferrous content of ferrous fumarate at the time of feeding. The ferrous retention rate reaching the corresponding release limit is taken as the chemical endpoint. When the ferrous iron retention rate does not reach the corresponding release limit, the corresponding batch will be transferred to the isolation state instead of using extended drying to replace the chemical endpoint determination. The preset drying temperature limit, drying oxygen limit, and release limits for drying loss, water activity, and ferrous iron retention are determined jointly by stability tests and dissolution consistency tests. Furthermore, sample labels are established at different spatial locations and discharge time periods in the granulation equipment, and each sample label is maintained with the corresponding composite particles until the same batch is dried. The test for the uniformity of the two iron sources includes taking samples from the same batch of composite particles that have reached the physical and chemical endpoints according to the sample identification, determining the content ratio of iron from ferrous fumarate and iron from sodium ferric ethylenediaminetetraacetate in each sample, and taking the relative standard deviation of the content ratio as being within the ratio uniformity limit determined by the unit dose iron content verification as the release condition for ratio uniformity. Color difference inspection uses the comprehensive color difference value under the same lighting conditions, and the condition for color difference release is that the comprehensive color difference value is within the color difference limit established by the qualified batch of process verification. The dissolution test measures the amount of elemental iron dissolved from multiple sampling units in a specified medium and at a specified sampling time. The release condition is that the relative standard deviation of each dissolution amount is within the limit determined by the dissolution consistency verification.

[0012] The beneficial effects of this invention are: 1. By first forming a ferrous fumarate core and then fixing ferric ethylenediaminetetraacetate at the surface dryness switching point, the time that ferric ethylenediaminetetraacetate is in the mobile wet phase can be shortened, and the risk of wet phase oxidation of ferrous fumarate can be reduced.

[0013] 2. By interlocking the spraying and inerting through the wet phase oxygen exposure index, and by adjusting the feeding and mixing cycle using the moving average and relative standard deviation of the spectral characteristics of the two iron sources respectively, the target ratio and spatial uniformity can be controlled simultaneously.

[0014] 3. By combining the dual physical endpoints of drying weight loss and water activity with the chemical endpoint of ferrous iron retention rate for drying and release determination, the batch-to-batch variation in valence state and migration caused by relying solely on time or a single moisture endpoint can be reduced, thereby improving storage stability, dissolution consistency and batch-to-batch reproducibility. Attached Figure Description

[0015] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a flowchart of the preparation method of the composite iron agent of ferrous fumarate and EDTA iron sodium in this invention.

[0016] Figure 2 This is a flowchart of the S3 surface dry switching point determination step of the present invention. Detailed Implementation

[0017] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, illustrating only the basic structure of the invention, and therefore only show the components relevant to the invention.

[0018] refer to Figures 1-2 A method for preparing a composite iron agent of ferrous fumarate and EDTA iron sodium, comprising: S1, determining the feeding amounts of ferrous fumarate and EDTA iron sodium according to the target element iron ratio, mixing EDTA iron sodium with a first carrier to obtain a post-dry powder premix, and using ferrous fumarate and a second carrier as pre-feeding components; S2, after inerting in a granulation device, using a deoxidizing adhesive to perform segmented spray granulation on the pre-feeding components to obtain a ferrous fumarate core; S3, determining the surface-dry switching point where the continuous liquid film on the surface of the ferrous fumarate core disappears but still has residual adhesion; S4, adding the post-dry powder premix after the surface-dry switching point, and using a deoxidizing adhesive for pulse spraying and mixing, so that EDTA iron sodium is fixed on the outer layer of the ferrous fumarate core, obtaining composite particles with two iron sources located in the same particle; S5, drying the composite particles within preset drying temperature and drying oxygen limits to obtain the finished composite iron agent.

[0019] In this specific embodiment, S1 includes: This specific implementation method uses the preparation of a batch of composite iron agent with a target finished product dry basis weight of 100.00 kg and a target total elemental iron weight of 10.00 kg as the same batch scenario from S1 to S5. The product formulation sets the target ratio of elemental iron from sodium ferric ethylenediaminetetraacetate to elemental iron from ferrous fumarate at 0.25, and the feed calculation adopts... and , This indicates the target mass of iron, the source element of ferrous fumarate, in kg. This indicates the total mass of iron, the target element in this batch, in kg. This represents the proportion of the target element iron in the two iron sources and is a dimensionless number. The target mass of iron from sodium ethylenediaminetetraacetate is expressed in kg, which gives the former as 8.00 kg and the latter as 2.00 kg. After the raw materials were released, the elemental iron content of ferrous fumarate and sodium ferric ethylenediaminetetraacetate was determined separately, and the theoretical feed mass was corrected using their respective elemental iron contents. Specifically, three parallel samples were taken from each of the two raw materials. The ferrous fumarate sample was subjected to cerium titration and total iron verification using a solution acidified with sulfuric acid and isolated from air. The sodium ferric ethylenediaminetetraacetate sample was extracted with water, and the coordinated iron was determined by HPLC-UV method, and the total iron was verified by ICP-OES. The measured elemental iron mass fractions in this batch were 32.80% and 13.25%, respectively. To ensure that the final state detection was not affected by coordination exchange... Furthermore, the stable iron isotope fingerprints of the two released feedstocks were determined using multi-detector ICP-MS. The 57Fe / 56Fe and 58Fe / 56Fe ratios of this batch of ferrous fumarate feedstock were 0.0248 and 0.0031, respectively, while the corresponding ratios of the sodium iron ethylenediaminetetraacetate feedstock were 0.0210 and 0.0102, respectively. The binary solution matrix composed of the two fingerprints was verified using seven known mixing ratio standards to uniquely invert the iron mass from both sources. If the source ratio recovery deviation of any standard exceeds 2.0%, this batch of feedstock should not be used for source ratio determination. Correct the feeding quality. Indicates the first The corrected feed mass of the iron source raw material, in kg. This batch represents the iron source index for ferrous fumarate or ferric sodium ethylenediaminetetraacetate, and is a dimensionless positive integer. Choose 1 or 2. Indicates the first The mass of elemental iron that should be contributed by the iron source, in kg. Indicates the first The measured mass fraction of iron in the iron source is dimensionless. This represents the loss rate of the iron source process determined by the recovery rate verification of three batches, and is a dimensionless number. The loss rates of ferrous fumarate and sodium iron ethylenediaminetetraacetate in this batch are taken as 0.008 and 0.005, respectively, resulting in corrected feed masses of 24.59 kg and 15.17 kg. If the relative deviation of any parallel measurement exceeds 2.0% or the corrected mass exceeds the weighing range of the weighing equipment, the weighing is suspended and the corresponding raw material is isolated. The entire process adopts a unified dry-basis metering standard. Three parallel samples are taken before each powder raw material is fed, and the moisture content is measured in a Karl Fischer furnace under dry nitrogen-carrying conditions at 80°C. Conversion; Expresses the dry weight of a material or sample, in kg. This indicates the actual wet basis weight of the same material or sample, in kg. This represents the measured moisture mass fraction at the corresponding sampling time, which is dimensionless and is derived from the average of the three parallel samples, satisfying the following conditions: The powder feed amount, premix amount, process sample loss, equipment residue, bulk particle amount and sample box amount listed below all refer to... The actual weighed mass is calculated by dividing the corresponding dry basis target mass by 1 / 2. Obtain and save batch records simultaneously , and If the relative deviation of any parallel measurement exceeds 2.0%, Not within the release range of the raw materials used or in the denominator Feeding should be suspended and the affected area isolated if the value is not greater than 0; this batch contains ferrous fumarate, sodium ferric ethylenediaminetetraacetate, the first carrier mixture, the second carrier, fumaric acid, and sodium citrate. The values ​​are 0.0120, 0.0350, 0.0400, 0.0450, 0.0050, and 0.0050, respectively. The corresponding actual wet basis weighing masses for the dry basis target quantities described later are 24.8887 kg, 15.7202 kg, 20.8333 kg, 42.2622 kg, 0.1176 kg, and 0.0392 kg, respectively. For each process sample, the moisture content or constant weight result of the same batch was used for recalculation at the time of sampling. Dry basis loss is only considered... Instead of including the periodic moisture content in the material loss; The first carrier was selected from at least one of microcrystalline cellulose, pregelatinized starch, maltodextrin, and mannitol. The carrier candidates were first filtered based on the following conditions: moisture content not exceeding 6.0%, a coordinated iron recovery rate not less than 98.0% after mixing with sodium ferric ethylenediaminetetraacetate (EDTA) for 24 hours, and a static angle of repose not exceeding 42°. They were then sorted by the relative standard deviation of ten premixing points from smallest to largest. If the relative standard deviations were the same, the carrier with the lowest moisture absorption increment was selected. This batch used a carrier mixture of pharmaceutical-grade microcrystalline cellulose and maltodextrin at a dry weight ratio of 1:1. The two carriers were first passed through a 40-mesh sieve. Then, in a 300 L V-shaped mixer, 15.17 kg of dry weight sodium ferric ethylenediaminetetraacetate (EDTA) and 20.00 kg of dry weight first carrier were combined in a geometrically increasing manner, with the loading coefficient controlled between 0.45 and 0.60. The mixer speed was set to 15 r / min. Samples were taken from the feeding end, middle, and discharge end every 5 minutes of mixing, for a total of 20 minutes, yielding 35.17 kg of dry weight. kg post-dry powder premix; Premix sampling employed a ten-point sampling map, with each of the ten samples uniquely identified by its premix batch number, spatial location, and sampling time. Each sample was measured synchronously. The dry basis weight was 20 g, and the actual wet basis weight was recorded for each sample. Ten dry basis samples totaled 0.20 kg. The samples were used for destructive testing and were not re-injected. After deducting 0.20 kg of the dry basis weight from the 35.17 kg dry basis weight of the premixed dry powder, a feedable net weight of 34.97 kg was obtained. After water extraction and filtration through a 0.45 μm filter membrane, the mass fraction of sodium EDTA was determined by HPLC-UV method. A five-point calibration curve was established for the chromatographic system using sodium EDTA reference standard with assigned content. The test data was accepted when the recovery rate was between 98.0% and 102.0% and the difference between parallel determinations did not exceed 2.0%. If the result was outside this range, the sample was re-prepared and retested. If the retest was still unqualified, the premix was isolated. The post-mixed dry powder premix is ​​only allowed to enter S4 if the relative standard deviation of the sodium ferric ethylenediaminetetraacetate content measured by multiple sampling points is within the premixing uniformity limit. The ten-point measurement values ​​are... Calculate the premixing uniformity. This indicates the relative standard deviation of the sodium iron ethylenediaminetetraacetate content in the post-processed dry powder premix, expressed in %. This represents the sample standard deviation of the ten content determination values, expressed in %. The arithmetic mean of the ten content determination values ​​is expressed in %. The target element iron ratio and the premix uniformity limit are determined by the product formulation and process validation results. In this formulation, the premix uniformity limit is set at 3.0%. The ten-point average content of this batch is 43.12% and the relative standard deviation is 1.58%. Therefore, the state of this premix is ​​marked as feedable. If it exceeds 3.0%, continue mixing for 5 minutes and retest once. If the retest still exceeds the limit, lock the feeder and place the premix in an isolated safe state. The second carrier is pregelatinized starch. 24.59 kg of ferrous fumarate and 40.3604 kg of pregelatinized starch are premixed in a closed hopper for 10 min to obtain 64.9504 kg of unadjusted premix. Ferrous fumarate and the second carrier are used as the main components of the pre-feeding component. This pre-feeding component is formed after the adjustment amount is determined in S2, the entire batch is added, and the retest is passed. In this batch, the S4 adhesive formula quota of 0.99 kg is pre-approved in S1 based on the three batches of process verification. This quota is covered by an independent closed supply of 1.00 kg of liquid, plus a 0.01 kg pipeline weighing balance. This quota is independent of subsequent feedback results from this batch. In the same batch, 5.60 kg of 4.0% povidone deoxygenated adhesive is prepared, of which 4.60 kg is specifically used for S2 segmented granulation with a povidone dry solids content of 0.184 kg, and 1.00 kg... S4 uses a separate, sealed container with the same master batch number. The S4 formulation quota of 0.99 kg contains 0.0396 kg of povidone dry solids. The remaining 0.01 kg is only used as a pipeline weighing margin and is sealed after S4 is completed, not included in the product. S2 adds 0.117 kg of fumaric acid and 0.039 kg of sodium citrate, scaled up to the actual mass of the unadjusted premix. The total dry solids of the two iron sources, the first carrier, the second carrier, the adjusting components, and the pre-approved formulation quotas of S2 and S4 amount to 100.50 kg. If the 0.99 kg formulation quota of S4 is not fully used, the mass of the S1 carrier cannot be inferred from the subsequent usage of this batch. Instead, release is suspended, and a dry basis check is performed based on the actual dry solids difference. If the difference is below 99.95 kg or above 100.05 kg, isolation is required. The 100.50 kg... kg represents the total dry basis weight before deducting non-reusable process samples and equipment residues. The batch record lists the following separately: S1 ten-point sample 0.20 kg, S2 pH sample 0.02 kg, S2 particle size sample 0.20 kg, S5 loss on drying sample 0.02 kg, water activity sample 0.05 kg, and equipment and transfer residues 0.01 kg, totaling 0.50 kg of dry material process loss. The nine space-time sample boxes are still included in the batch dry basis weight before destructive release testing. Therefore, the target batch dry basis weight when the full prescription quota is used and drying is completed is 100.00 kg. The batch record includes the batch number of each material, dry basis weight, binder distribution amount, S4 pre-approved quota, actual usage, remaining amount, each loss item and weighing verification result, and is associated with the subsequent dry powder premix, deoxidized binder and subsequent granulation data under the same master batch number. The measured mass fraction of sodium iron ethylenediaminetetraacetate in the post-processed dry powder premix was recorded as 43.12%, and the upper limit for calculating the feed content was based on... calculate, This indicates the maximum cumulative feed amount of the post-processed dry powder premix, calculated based on content, in kg. This indicates the mass of sodium iron ethylenediaminetetraacetate (EDTA) fed after S1 correction, in kg. This represents the measured mass fraction of ferric sodium ethylenediaminetetraacetate in the post-processed dry powder premix, and is a dimensionless number. This indicates the permissible deviation for forward feeding determined by process validation, and it is a dimensionless number. For this batch, it is taken as 0.010, resulting in an upper limit of 35.53 kg for content calculation. The control system then takes the minimum value between this 35.53 kg and the net feedable amount of 34.97 kg, and determines 34.97 kg as the effective total feed limit for this batch. This limit, the target ratio of 0.25, the allowable range of the conversion domain of 0.238 to 0.263, the allowable range of the ratio domain calculated from SP-05 of 0.891 to 0.992, and the two relative standard deviation limits of 4.0% and 4.3% are written into the S4 control parameter file. The S4 control parameter file also includes a dual-domain control predicate for a continuously moving window. When the moving average of the ratio of spectral feature scores is less than 0.891 and the moving average of the predicted elemental iron ratio converted by SP-05 is less than 0.238, the feed rate of the post-dry powder premix per unit time is increased to 1.20 kg / min. The rules described in the weights are applied to the conversion domain, i.e., feeding is paused when the moving average is greater than the upper limit of the target ratio range or when the moving average is within the target ratio range. The moving average of the ratio domain is required to be simultaneously greater than 0.992 or in the corresponding state between 0.891 and 0.992. When the moving average is exactly equal to the upper or lower limit, it is treated as being within the range and feeding is paused. When the range determinations of the two domains are inconsistent, the window is invalid and feeding is paused. Manual sorting or undefined parallel rules are not used. When the relative standard deviation of the ratio range is greater than 4.3% or the relative standard deviation of the conversion range is greater than 4.0%, under the condition of maintaining the feeding state jointly determined by the two moving averages, the non-spraying mixing time is extended from 60 s to 120 s and the single pulse spray volume is reduced from 60 g to 30 g; the fixing process of sodium iron ethylenediaminetetraacetate is only ended after the two moving averages and two relative standard deviations of three consecutive moving windows are qualified. The number of consecutive windows is determined by the verification lower boundary with a false judgment probability of no more than 1.0%. When the cumulative feeding amount reaches the total feeding limit or the 35-minute preset control time limit expires and the moving average or relative standard deviation of any domain is still unqualified, the S4 control parameter file requires stopping feeding and spraying and transferring the corresponding batch to the isolation state. The loss-in-weight feeder is closed, the spraying valve is closed, the stirring is maintained at 80 r / min and the nitrogen is maintained at 20 m3 / h to form the isolation safety state. Batches that meet the verified rework conditions are reworked once according to the target element iron ratio, drying loss and ferrous iron retention rate safety thresholds. If any safety threshold is not met, it will not enter the production process. At the end of S1, the electronic batch record generates three controlled objects: the unadjusted premix, the post-dry powder premix, and the S4 feeding control parameter file. All three share the main batch number FB-EDTA-260808. The ten-point uniformity results of the premix, the iron source correction feed amount, and the total feed limit are all verified by two people. Then, the unadjusted premix is ​​transferred to the S2 closed pH adjustment station, the post-dry powder premix is ​​placed in the loss-in-weight feeder for use, and the control parameter file is transmitted to the process control systems from S2 to S5.

[0020] In this specific embodiment, S2 includes: This specific implementation uses a 300 L high-shear granulation device equipped with a closed-loop nitrogen purging system, a top spray gun, a near-infrared probe, an oxygen analyzer, a particle temperature probe, a stirring power acquisition device, and an exhaust dew point meter. After the equipment is cleaned and confirmed, nitrogen with a purity of not less than 99.999% is used to purge from the bottom, inerting the granulation device until the oxygen volume fraction is within the preset oxygen limit. The oxygen analyzer records the oxygen volume fraction every 5 seconds, and inerting is considered complete when the reading is not higher than 1.0% for 60 consecutive seconds. The inerting reference oxygen volume fraction before adding the pre-feeding components in this batch is 0.42%. The deoxygenated adhesive was prepared using deoxygenated water obtained by passing nitrogen through purified water at 20-25°C for 30 minutes. The dissolved oxygen limit of the deoxygenated water was 0.50 mg / L. Pharmaceutical-grade povidone was added to a closed mixing tank to achieve a mass fraction of 4.0%. This povidone used raw materials with an average relative molecular mass grade of 30. The mixture was stirred at 80 r / min for 20 minutes and then allowed to stand to remove bubbles. The total preparation quantity for this batch was 5.60 kg. After preparation, 4.60 kg was dispensed into the S2 granulation supply container and 1.00 kg into the S4 pulse supply container via two calibrated closed weighing branches. The pre-approved quota for the S4 branch was 0.99 kg, with an additional 0.01 kg pipeline weighing margin. Both containers were recorded with the main batch number FB-EDTA-260808, initial net weight, and intended use, and no liquid replenishment was allowed between them. The vapor space of the mixing tank, the diaphragm pump inlet, the delivery hose, and the spray gun return end were all maintained at 5-15°C. kPa nitrogen positive pressure, the online dissolved oxygen probe is checked after the solution preparation is completed and before the liquid spraying of each branch starts. If any reading exceeds 0.50 mg / L, the corresponding branch liquid supply is stopped and deoxygenation is restarted. The microenvironment pH was adjusted using a regulating component composed of fumaric acid and sodium citrate. Process validation was conducted by establishing a regulation amount record table in response to the ferrous fumarate retention rate. The table fields included the unregulated premix batch number, fixed solid-liquid mass ratio, measurement temperature, settling time, initial pH, unit solid regulation amount, retested pH, and 24-hour ferrous retention rate. The record table was updated annually or whenever any raw material supplier changed. For this batch, 10.0 g of representative dry-basis sample was obtained by combining equal amounts from the upper, middle, and lower portions of the unregulated premix obtained from S1. The actual wet-basis weighing mass was based on the synchronous measurement of S1. The sample was converted and recorded as being used for destructive testing and not re-injected. It formed a dispersion with a dry basis solid-liquid mass ratio of 1:10 with 100.0 g of deoxygenated water. After stirring at 300 r / min for 2 min at 25.0±0.5℃ and standing for 10 min, the pH was measured to be 5.18. The controlled record corresponding to the initial pH of 5.0 to 5.3 in the adjustment record table is as follows: 18.0 mg of dry-based fumaric acid and 6.0 mg of dry-based sodium citrate are added to every 10 g of unadjusted premix on a dry basis. Based on the dry-based mass of 64.9504 kg of the unadjusted premix in this batch, 0.117 kg of dry-based fumaric acid and 0.039 kg of dry-based sodium citrate are obtained. These two components are weighed according to the wet-based mass given in S1 and added evenly in a closed hopper and mixed for 5 min to form the premix component. Then, equal amounts are combined from the top, middle, and bottom portions to obtain 10.0 g of dry-based sample without re-addition. The actual wet-based mass is measured synchronously. After conversion, the pH was retested with the same dry basis solid-liquid mass ratio, temperature and standing time, and the result was 4.36. The total dry basis of the two pH samples was 0.02 kg, and the batch dry material loss was included. The retested value fell within the stable range of 4.20 to 4.60 determined by the oxygen volume fraction gradient test and the 24-hour ferrous iron retention rate test, and the 24-hour ferrous iron retention rate was 98.7%. If the retested value was not in the stable range, the component would not be fed into the granulation equipment and would be transferred to the deviation investigation. The pre-feed components, after being adjusted and retested to meet standards, were added to the inerted equipment. Dry mixing was performed for 5 minutes at 120 r / min with the agitator and 800 r / min with the cutter. The liquid was then sprayed in stages: nucleation, growth, and shaping. In the nucleation stage, liquid was sprayed at 0.25 kg / min for 4 minutes and mixed for 1 minute. In the growth stage, liquid was effectively sprayed at 0.35 kg / min for 8 minutes, with a 30-second pause every 2 minutes of spraying. In the shaping stage, liquid was sprayed at 0.20 kg / min for 4 minutes and mixed for 3 minutes. The total effective liquid volume for the three stages was 4.60 kg, containing 0.184 kg of dry povidone solids. The spray gun atomization pressure was 0.25 MPa, and the median droplet diameter was controlled between 60 and 100 mm. μm, during the segmented spray granulation process, the particle temperature is maintained within the preset granulation temperature limit, and the jacket cooling ensures that the particle temperature does not exceed 32℃. This temperature limit and the 1.0% oxygen volume fraction limit are respectively taken from the boundary where the ferrous iron retention rate is not less than 97.0% in the temperature gradient and oxygen gradient tests. The critical value for continuous liquid film was established using five calibration batches of samples with continuous liquid film on the surface and five calibration batches of samples without continuous liquid film. Reflectance spectra from 1000 to 2200 nm were acquired using the same near-infrared probe and processed with standard normal variables and first derivatives. A liquid film disappearance label was defined as a continuous reflective area accounting for less than 5% of the particle surface imaging and adjacent images no longer being connected. The resulting near-infrared prediction of moisture content was a two-class boundary value of 9.0%. This 9.0% was incorporated into the control system as the critical value for continuous liquid film. The model was cross-validated with one batch retained, and the accuracy rate for liquid film state classification was 96.4%. Every 5-second sampling interval, oxygen volume fraction, near-infrared predicted moisture content, and particle temperature are written into the synchronous data set. When the near-infrared predicted moisture content is not higher than 9.0% or the measured oxygen volume fraction is not higher than the inerting baseline, the contribution of wet phase oxygen exposure in this interval is recorded as zero. When the near-infrared predicted moisture content is higher than 9.0% and the measured oxygen volume fraction is higher than the inerting baseline, it is recorded as zero. calculate, Indicates the first The contribution of wet phase oxygen exposure per sampling interval, expressed as volume percentage per min. This represents a dimensionless positive integer representing the sampling interval index that increases with time and starts from 1. Indicates the first The measured oxygen volume fraction at each sampling interval, in %. This indicates the volume fraction of inerting reference oxygen before feeding, in percentage. Indicates by the first Dimensionless oxidation rate correction factor determined by particle temperature at each sampling interval Indicates the first Particle temperature at each sampling interval, in °C. This represents the sampling interval and is converted to min; for this batch, it is 0.0833 min. The oxidation rate correction factor was fitted from wet-phase oxidation tests of ferrous fumarate at 25, 28, 30, and 32 °C and stored in a temperature correction table (version OT-03). The lookup key in the table was particle temperature, and linear interpolation between adjacent temperatures was used. Each record contained a correction factor of 1.28 for 30 °C, an effective temperature range of 29 to 31 °C, and the ferrous retention rate test batch number. Temperatures exceeding the 25 to 32 °C range were calculated using the most unfavorable factor of 1.50 and simultaneously triggered a temperature deviation. The cumulative wet-phase oxygen exposure index was calculated as follows: renew, Indicates as of the date The cumulative wet phase oxygen exposure index for each sampling interval, expressed as a volume percentage per minute. This represents the total number of sampling intervals accumulated so far, and is a dimensionless positive integer count. and The meaning follows the direct definition mentioned above; Batch validation sets the first interlock threshold, the second interlock threshold, and the preset exposure limit to 2.0, 4.0, and 6.0 volume percentages per minute, respectively. When the cumulative index reaches 2.0, the spray duty cycle is reduced to 70% of the current value, and the nitrogen replacement flow rate is increased from 18 m³ / h to 25 m³ / h. When it reaches 4.0, spraying is immediately stopped while maintaining stirring and a nitrogen flow rate of 25 m³ / h, and the cumulative value does not regress. An oxygen volume fraction not exceeding 0.60% for 60 consecutive seconds and a near-infrared predicted moisture content not exceeding 9.0% only constitute the second interlock reset condition. After reset, the control system must also verify the actual and remaining liquid volumes in the nucleation, growth, and shaping stages; whether the cumulative S2 liquid consumption reaches 4.60 kg; the results of the 16-mesh sieve and 40-mesh sieve; the median particle size; and the nucleus integrity endpoint. Only when the specified doses for each segment have been completed and the cumulative S2 liquid consumption is exactly 4.60 kg will the system be able to achieve the desired result. The qualification signal for entering the S3 surface drying judgment is sent only when the volume of liquid remains in any segment, the cumulative liquid usage is less than 4.60 kg, or the nuclear endpoint is not qualified. If there is still residual liquid in any segment, the cumulative liquid usage is less than 4.60 kg, or the nuclear endpoint is not qualified, the liquid supply valve is closed and the batch is transferred to the isolation final state. The remaining sprayed liquid is not restored, and the batch is not entered into S3 to S5. The actual used adhesive liquid and its povidone solids are only recorded in the isolation batch material ledger and the 4.60 kg input of the qualified batch is not used. When the value reaches 6.0, the liquid supply valve is closed and the batch status is set to isolation. The threshold is derived from the three-batch verification curve of wet phase oxygen exposure index and ferrous iron retention rate, and the lower confidence limit of ferrous iron retention rate corresponding to 4.0 is still higher than 97.0%. The granulation process also involves sieving samples every 2 minutes, with a dry basis weight of 20 g (corrected for moisture content by synchronous near-infrared spectroscopy) to confirm particle size growth. Actual wet basis weight and conversion are also used. Record each step. A total of ten sieves were taken throughout the entire process, with a dry basis of 0.20 kg. All samples were used for destructive sieve testing and were not recycled. The dry material loss of the batch was included in the process loss. When the amount of material on the 16-mesh sieve exceeded 20%, the spraying was stopped and stirring was maintained for 2 minutes. When the amount of material under the 40-mesh sieve exceeded 25%, the spraying rate of the nucleation section was resumed, but not exceeding 0.25 kg / min. Any adjustment must simultaneously meet the requirements that the oxygen volume fraction is not higher than 1.0% and the particle temperature is not higher than 32℃. Otherwise, the safety state of stopping the spraying, nitrogen at 25 m3 / h and stirring at 120 r / min was maintained. After the temperature and oxygen conditions were restored, the process continued from the current remaining liquid volume without recalculating the accumulated wet phase oxygen exposure index. During the nucleation and growth process of this batch, the peak temperature of the particles was 30.8℃, the peak oxygen volume fraction was 0.88%, and the cumulative wet phase oxygen exposure index was 1.72 volume percentages·min, which did not reach the first interlocking threshold. After shaping, the particles were granulated through a 16-mesh screen to obtain ferrous fumarate nuclei with a median particle size of 420 μm and a water content close to the critical value of continuous liquid film along the decreasing direction. The particle batch number, synchronous data group, temperature correction table version, and non-regressing cumulative wet phase oxygen exposure index were then transferred to S3.

[0021] In this specific embodiment, S3 includes: In this specific implementation, during the process verification stage, samples were taken from three batches of ferrous fumarate cores every 30 seconds. The samples were placed in a closed nitrogen observation chamber and particle surface images were acquired under fixed ring illumination, fixed camera exposure, and fixed magnification. The continuous high-light region was binarized and connected component analysis was performed. The calibration time when the continuous reflective region accounted for less than 5% of the visible surface area of ​​the particle and there were no connected liquid bridges crossing adjacent particles at three consecutive sampling times was taken as the time when the continuous liquid film on the surface disappeared. Residual adhesion was determined using pharmaceutical lactose standard probe powder, which was used only for calibration and not included in the product batch. The median particle size of the probe powder was 40 μm. 2.00 g of probe powder was added to each 100 g calibration granules and mixed at 60 r / min for 30 s under nitrogen protection. After sieving to remove unadhered probe powder, the mixture was then... Calculate the adhesion ratio. This indicates the percentage of standard probe powder adhered to the surface. The mass of the particles after mixing and sieving to remove free probe powder is expressed in grams. This indicates the particle mass before the addition of probe powder, in grams. The amount represents the mass of the added standard probe powder, expressed in grams. The process validation determined the adhesion ratio of 4.0% to 10.0% as the acceptable period for residual adhesion. Align the liquid film disappearance calibration time and the residual adhesion qualified time period with the synchronously collected near-infrared predicted moisture, stirring power and exhaust absolute moisture content to obtain the near-infrared predicted moisture in the downward direction as the entry boundary 9.0% and the exit boundary 7.2%. The 7.2% to 9.0% range is used as the surface dryness judgment interval. The boundary is taken as the inner value of the overlapping interval where the liquid film disappearance and probe powder adhesion qualified are satisfied in the three batches of calibration. Any near-infrared model update uses the original calibration sample to reconfirm these two boundaries. Before each batch of online near-infrared probes, background calibration is performed using a polytetrafluoroethylene white board. The power acquisition unit is checked at two points: no load and standard load. The exhaust dew point meter is checked at the saturated salt humidity point. If any check deviation exceeds 2.0% of its respective range, the surface dryness judgment must not be initiated. If the residual of three consecutive near-infrared spectra exceeds the model control limit during operation, the time period is marked as invalid and kept mixed and inert. The judgment window is restarted after the probe window is cleaned and checked with calibration particles. The process control system calculates the rate of change of stirring power using a 120-second decision time window. and the rate of change of absolute moisture content in exhaust air , This indicates the relative rate of change of stirring power within the judgment time window, expressed in % / min. This indicates the stirring power at the end of the time window, in kW. This indicates the initial stirring power of the time window, in kW, and must be greater than zero and not less than the minimum effective power of 0.10 kW determined by the power acquisition unit under no-load and standard load verification. This indicates the length of the decision time window, in minutes, and for this batch it is 2 minutes. This indicates the rate of change in absolute moisture content of exhaust air, expressed in g / kg dry air / min. This indicates the absolute moisture content of the exhaust air at the end of the time window, expressed in g / kg dry air. This indicates the absolute moisture content of the exhaust air at the start of the time window, expressed in g / kg dry air; when If the value is below 0.10 kW, zero or negative values ​​are found, or the power acquisition unit reports an abnormality, the current judgment window is marked as invalid, and mixing at 120 r / min and nitrogen inerting at 18 m3 / h are maintained. The full window counting will restart after the power acquisition unit is verified and restored. When the near-infrared predicted moisture content is between 7.2% and 9.0%, the relative change rate of stirring power is between -0.50% / min and 0.50% / min, and the change rate of absolute moisture content in the exhaust air is not greater than 0.10 g / kg dry air / min, the current window is recorded as a qualified window. After three consecutive qualified windows, a surface dryness switching event is generated. The event record includes the main batch number, switching time, near-infrared predicted moisture content, power change rate, change rate of absolute moisture content in the exhaust air, oxygen volume fraction in the equipment, particle temperature, and cumulative wet phase oxygen exposure index. The three criteria use the same 5-second timestamp data instead of manual observation. When the near-infrared predicted moisture content is still higher than 9.0%, maintain stirring at 120 r / min and nitrogen replacement at 18 m3 / h without adding post-dry powder premix, and continue to execute the wet phase oxygen exposure index interlock established in S2. When the cumulative index reaches the first interlock threshold, execute actions to reduce the spray duty cycle and increase the nitrogen flow rate. When the second interlock threshold is reached, stop spraying and keep the cumulative value from regressing. Only when the oxygen volume fraction is not higher than 0.60% and the near-infrared predicted moisture content is not higher than 9.0% will the qualified window counting restart. Once the preset exposure limit is reached, it will not enter S4. The first interlock threshold, the second interlock threshold, the reset oxygen limit, and the preset exposure limit are all read from the verification parameter record of version OT-03. The record uses the wet phase oxygen exposure index as the lookup key and saves the mean ferrous retention rate, the lower confidence limit, and the release limit. If the first interlock threshold is less than the second interlock threshold and the second interlock threshold is less than the preset exposure limit, or if the parameter file version is inconsistent, the threshold order is incorrect, or the lower confidence limit of the ferrous retention rate corresponding to the second interlock threshold is less than 97.0%, the system refuses to generate a surface dry switch event. A 15-minute preset waiting time limit is set from the end of the shaping section. If the near-infrared predicted moisture content exceeds 7.2% in the downward direction but three consecutive qualified windows have not been formed, or if the three criteria are not met simultaneously when the waiting time limit expires, the post-feeder and spray valve are closed, the corresponding batch is transferred to the isolation state, and the ferrous fumarate core and the full-volume synchronous data set are locked. The isolated batch is only allowed to be rehumidified once in an oxygen volume fraction below 0.60% if the cumulative wet phase oxygen exposure index is less than 6.0 volume percentage·min, the near-infrared ferrous retention rate is not less than 97.0%, and the target element iron ratio can still be traced after rework. Otherwise, it is treated as unqualified. In the isolation safety mode, the feeder is powered off, the spray valve is closed, stirring is at 80 r / min, and nitrogen is at 20 m3 / h. Quality personnel obtain a near-line ferrous sample within 30 minutes and verify the cumulative index. When readjustment is permitted, only the 1.00 kg sealed supply container of S2, already dispensed to S4 according to the same master batch number, is used. No additional binder is prepared or introduced. A controlled pulse is defined as 30 g. A maximum of three pulses are executed under the conditions of oxygen volume fraction not exceeding 0.60% and mixing at 80 r / min. After each pulse, there is no spray mixing for 60 seconds, and the near-infrared predicted moisture content is read. Liquid addition is stopped when the moisture content reaches 8.10% to 8.50%. The total amount of the three pulses is a maximum of 90 g, which is 2.0% lower than the total amount of the same batch of deoxidized binder (5.60 kg) of S2. The actual number of pulses is recorded as follows: It is a dimensionless non-negative integer of 0, 1, 2, or 3, where 0 indicates that readjustment was not triggered and the actual amount of S3 used is 0.03. The dry solids content of povidone is 0.0012 kg. kg, the wet liquid and dry solids used are both reduced by an equal amount from the pre-approved 0.99 kg formulation quota of S4 and the 0.0396 kg of povidone dry solids therein, so that the total of S3 and S4 shall not exceed the stated quota and shall not change the initial dry basis total of 100.50 kg of S1; the control system shall The actual wet volume, dry solids volume, and remaining S4 quota are written into the batch record. Based on this, the S4 execution table retains the first 13 60 g prescription doses and reduces the last 30 g prescription doses from 7 to [number missing]. The total amount of liquid used for S3 and S4 should be exactly 0.99 kg; the total mixing time of the re-humidified non-sprayed liquid should not exceed 5 minutes, and then the three complete 120-second surface drying window judgments should be performed again. If any of the temperature and oxygen, ferrous iron retention rate, quota accounting or surface drying criteria fails after rework, the rework should be terminated and isolation should be maintained. After the surface dry switching, the stirring speed is reduced from 120 r / min to 80 r / min, and the oxygen volume fraction of the equipment is kept not higher than 1.0% and the particle temperature is not higher than 32℃. The control system freezes the original data of the last qualified window before the switching and sends a feeding permission signal to S4. If any of the feeding permission signal, the total feeding limit of S1, or the feeding status of the post-dry powder premix is ​​missing, the feeder keeps the hardware interlock closed. This batch reached the surface-dry switching point 6.5 minutes after the shaping was completed. The near-infrared predicted moisture content of the three consecutive qualified windows was 8.54%, 8.41%, and 8.29%. The absolute value of the relative change rate of stirring power did not exceed 0.31% / min, the absolute change rate of exhaust air moisture content did not exceed 0.06 g / kg dry air / min, and the oxygen volume fraction of the equipment was 0.55%. The generated surface-dry switching event number was FB-EDTA-260808-SW and was used as the start timestamp of the S4 post-layering.

[0022] In this specific embodiment, S4 includes: In this specific implementation, upon receiving the S3 allow feeding signal, a controlled initialization state is first established, and a 35-minute control time limit is simultaneously initiated. Under the conditions that the cumulative feeding volume and cumulative spray volume are both zero, the feeder and spray valve remain closed, mixing is performed at 80 r / min, the oxygen volume fraction in the equipment is not higher than 1.0%, and the particle temperature is not higher than 32℃, probe purging, whiteboard calibration, and actuator no-load self-test are completed. Subsequently, the calibrated loss-in-weight feeder is activated, feeding the S1 post-dry powder premix into the ferrous fumarate core bed at an initial rate of 1.20 kg / min, while simultaneously using the same batch of deoxidizing binder (S2) for pulse spraying. The first 5 minutes from the initial feeding to obtaining 30 effective spectra constitute the initial sampling phase. Before the formation of the first window, the four dual-domain statistical fields are uniformly marked as initialization rather than as missing fields, and the feeding rate is fixed at 1.20 kg / min. The spraying rate is kg / min, and the prescription spraying is strictly executed according to the pre-approved dosage. Only four types of hard interlocks are accepted: temperature and oxygen safety, cumulative feed limit, cumulative binder quota, and equipment operation. After the first 30 effective spectral windows are formed, the dual-domain statistics are calculated immediately and the process is entered into a closed loop. The feed rate, prescription dosage, liquid volume, and 5-minute time consumption during the sampling phase are all included in the cumulative account and the 35-minute time limit. No separate seed feeding is set for unrecorded feed. A basic execution cycle is fixed at 90 seconds, which includes 5 seconds of spraying, 25 seconds of liquid stoppage, and 60 seconds of mixing without spraying. The online probe is used every 10 seconds during the entire mixing period. Continuous spectral acquisition is performed. Before the first window is formed, only temperature, oxygen, cumulative volume, and remaining time are updated at the end of each cycle. After the first window is formed, the complete control status is updated at the end of the cycle using the 30 most recent valid spectra. The prescription dose count and the qualification of the moving window are independent of each other. Each pulse is written into the cumulative count as soon as it starts, and it is not canceled due to subsequent invalid windows or excessive dispersion. Batches that have not undergone S3 re-humidification are executed according to the 0.99 kg prescription quota pre-approved by the three-batch process validation, including the first 13 60 g prescription doses and the last 7 30 g prescription doses. Batches that have undergone S3 re-humidification are read... And administer the first 13 60 g prescription doses and the subsequent... For each 30 g prescription dose, the total actual liquid used in S3 and S4 must be equal to 0.99 kg and must not exceed this value; the phased reduction is used to allow a small amount of adhesive liquid to form discrete adhesion points without restoring the continuous liquid film across particles, and is independent of the relative standard deviation anomaly branch; any next pulse can only begin after the previous basic execution cycle and its possible extended mixing are completed, the control state is reactivated and verified by the remaining time limit, and the no-spray mixing period is not allowed to overlap with the next pulse; Spectral calibration was performed using ferrous fumarate calibrated samples with assigned content values, sodium ferric ethylenediaminetetraacetate calibrated samples, and seven levels of composite particles with elemental iron ratios of 0.15, 0.18, 0.20, 0.23, 0.25, 0.28, and 0.30. Reflectance spectra were collected in the range of 1000 to 2200 nm for each calibration level, with three batches and six spatial locations per batch. After standard normal variable scattering correction, second-order Savitzky-Golay derivative, and local baseline subtraction, 1660 to 1720 nm was determined as the first characteristic band of the fumarate response, and 2110 to 2180 nm was determined as the second characteristic band of the ethylenediaminetetraacetate coordination structure response. The band positions were verified by the original calibration samples when the probe was changed, and were not changed by single production data. Before online spectral acquisition, the probe window was purged with dust-free nitrogen and the background was updated with a whiteboard. After acquisition, invalid spectra with a probe obstruction rate exceeding 10%, more than three full-spectrum saturation points, or model residuals exceeding 95% of the control limit were removed. Then, 30 valid spectra were acquired again according to the timestamp until the window contained 30 valid spectra. Abnormal states were classified into four categories: transient spectrum invalidity, probe or acquisition chain failure, SP-05 model access failure, and missing control fields or infeasible actions. If three consecutive acquisitions still did not reach 30 spectra, it was considered an upgraded transient spectrum invalidity state. At this time, feeding and spraying were suspended, mixing was maintained at 80 r / min, and nitrogen flow rate was 20 m³ / h. Immediately, three parallel positioning samples were taken from each of the three sealed sampling ports (upper, middle, and lower layers), totaling nine samples. Each sample was converted from the actual wet basis weight to a dry basis target of 10.0 g based on the synchronous moisture result. The nine samples, with a total dry basis of 0.090 kg, were immediately returned and used for destructive testing without re-injection. The number of immediate returns was recorded as follows: It is a dimensionless non-negative integer of 0, 1, or 2, where 0 indicates that immediate rollback was not triggered. For each completed sampling, 0.090 kg is deducted from the master batch dry basis account, and the accumulated rollback loss of 0.090 kg is recorded. The weight (kg), wet basis weight of nine portions, synchronous moisture content, and dry basis weight are recorded in the S5 material ledger. This sampling loss will not be compensated for with additional materials after production resumes. The expected batch dry basis weight before destructive release inspection is adjusted accordingly from 100.00 kg to [missing data]. kg; all nine immediate return samples were analyzed using multi-detector ICP-MS to determine 57Fe / 56Fe and 58Fe / 56Fe. The binary solution matrix, validated by the measured isotopic fingerprints of the two release materials locked in S1 and seven known mixing ratio standards, was used to directly invert the mass of iron from ferrous fumarate and the mass of iron from sodium EDTA in each sample and calculate their ratios. Additionally, EDTA-coordinated iron was determined by HPLC-ICP-MS, and total iron was determined by ICP-OES. These two results were used only for verifying coordination speciation and total amount and did not replace the source iron ratio. The spiked recovery rate of each sample must be above 97%. The standardization residual of the isotope binary solution must not exceed 2.0% for the content of iron in the sample. If any condition is not met, feeding and spraying should be stopped and the batch should be transferred to the isolation safety state. The average value of the iron content of the nine sources should be between 0.238 and 0.263 and the relative standard deviation should not exceed 4.0%. This only proves that the current material condition is qualified and is not a sufficient condition for restoring online control. Online control can only be restored after the probe cleaning and whiteboard calibration are completed, 30 valid spectra are obtained again, the qualified SP-05 model is confirmed to be loaded, and all fields and execution actions are self-tested and passed. The restoration operation can be performed a maximum of two times and should not exceed 15 minutes from the first pause. If the same fault occurs again after the second restoration, no third set of samples should be taken and the batch should be directly transferred to the isolation safety state. If any near-line condition is not qualified or the condition is not restored by the deadline, feeding and spraying should be stopped and the batch should be transferred to the isolation safety state. The immediate return sample uses the FB prefix and does not replace the space-time release sample established after the fixation is completed. For each corrected spectrum, within each characteristic band, according to Calculate spectral feature scores. Indicates band category The average corrected response value is a dimensionless number. This indicates the dimensionless category index for either the first characteristic band F or the second characteristic band E; in this batch, F or E is used. Indicates band category The set of wavelengths included, in nm. The wavelength within the set is represented in nm. Indicates wavelength The dimensionless absorbance response after scattering and baseline correction. Indicates band category The number of wavelength points included is a dimensionless integer. If the correction response exceeds the calibration range, the spectrum is marked as invalid and immediately resampled. The ratio of spectral feature scores by calculate, This represents the ratio of the spectral feature scores of the second characteristic band to those of the first characteristic band, and is a dimensionless number. This represents the average corrected response value of the second characteristic band, and is a dimensionless number. This represents the average corrected response value of the first characteristic band, and is a dimensionless number. The smoothed denominator value, representing a dimensionless positive number, is selected from three candidate values ​​(0.005, 0.010, and 0.020) based on the stability verification of the denominator in the seven-level calibration spectra. This selection ensures that all valid calibration spectra satisfy the desired result. The minimum value is taken as 0.010 in this batch; the measured denominator If the value is below 0.008, including zero and negative values, the spectrum is considered invalid and a second sample is taken. If the requirement is not met after three consecutive attempts, the sample is transferred to the aforementioned instantaneous near-line measurement branch. The elemental iron ratio of the calibrated particles is determined according to... Assignment, This represents the elemental ratio of iron derived from sodium ferric ethylenediaminetetraacetate to iron derived from ferrous fumarate, and is a dimensionless number. and The numbers represent the mass of elemental iron contributed by the two iron sources, both in kg. The seventh-level calibration data was established using weighted least squares. The correspondence, This represents the proportion of iron in the element predicted by the ratio of spectral feature scores, and is a dimensionless number. This represents the linear calibration intercept, which is dimensionless. This represents the linear calibration slope and is a dimensionless number. The ratio of the aforementioned spectral feature scores is obtained by the device model. It is 0.018. The coefficient of determination for the independent validation set is 0.247, the root mean square error of the proportional prediction is 0.982, and the root mean square error of the proportional prediction is 0.009. The model is loaded only when the root mean square error does not exceed 0.010 and the seven-level deviations do not exceed 0.015. Exceeding any of these limits constitutes a model admission failure. The feeder and spray valve remain locked. Nearline measurements are only used to determine the current material destination and must not replace model loading. Recalibration is performed at most once and must be completed within 15 minutes. If the admission conditions are still not met, the batch is transferred to an isolated safety state. The model file is locked by calibration batch, instrument serial number, and version SP-05. The online probe acquires one valid spectrum every 10 seconds, and 30 consecutive valid spectra constitute a 5-minute moving window. First, press [the button]. and Update the moving statistics of the ratio of spectral feature scores; This represents the moving average of the ratios of spectral feature scores within the window, and is a dimensionless number. The relative standard deviation of the ratio is expressed in %. Indicates the window The sample standard deviation is a dimensionless number. The window is arranged by time from 1 to... The dimensionless positive integer index of the value, Indicates the first The ratio of the characteristic scores of the spectra is a dimensionless number. This indicates the number of valid spectral lines within the window and is a dimensionless positive integer; in this batch, it is 30. Only... Calculation is only performed when the value is greater than 0.05. , If the value is zero, negative, or not greater than 0.05, the current window is deemed invalid and the aforementioned supplementary sampling and immediate near-line branch are initiated; simultaneously, calculations are performed using the SP-05 model. Press again and Update the physical proportional control value. Indicates the first The spectrum is as described above and The predicted iron ratio, calculated from the model parameters, is a dimensionless number. This represents the dimensionless moving average of the predicted iron content within the window. This represents the relative standard deviation of the predicted iron content within the window, expressed as a percentage. This represents the sample standard deviation of the predicted iron proportion within the window and is a dimensionless number. and The spectral ratio range statistics constitute the weights mentioned above. and The conversion domain statistics correspond to the iron ratio of the product's target element; both domain statistics are retained without substitution. The control state is... , , , The system consists of six fields: cumulative feeding amount, remaining control time, etc. It is updated every 10 seconds and outputs four action fields: feeding switch, feeding rate, pulse quantity, and mixing duration. If a field is missing or the action exceeds the equipment limit, feeding and spraying are immediately suspended and field reconstruction, communication verification, and actuator no-load self-test are performed. This is done at most twice and the cumulative time does not exceed 10 minutes. The system will only resume when all six status fields and four action fields are complete and the action is within the equipment limit. If the system still fails to pass the time limit, it will enter the isolation safety state. The target ratio range corresponding to the S1 target element iron ratio of 0.25 is set to 0.238 to 0.263. Based on the locked SP-05 relationship, this range is calculated in reverse. The target range is 0.891 to 0.992. In this specific implementation, the maximum relative standard deviation allowed for the uniformity verification of iron content per unit dose is used as the spatial uniformity limit. Specifically, the same set of uniformity verification data per unit dose described in S5 is used, and the process control limit for the source iron ratio is set to... Not exceeding 4.0%, and obtained from SP-05 calibration error propagation. The ratio limit is no more than 4.3%; when Less than 0.891 and corresponding When the feed rate is less than 0.238, maintain or increase the feeder speed to 1.20 kg / min. Greater than 0.992 or between 0.891 and 0.992 and corresponding When the synchronization is within the corresponding interval, a pause feeding action is generated; the feeding action is a 10-second indivisible measurement command. When the current window is updated, only the next 10-second command is determined. The 10-second feeding command issued at the previous update timestamp must be executed and included in the cumulative quantity. The pause action cannot be interrupted in the middle of the command, and no new feeding command can be issued after the action takes effect; if the two domain intervals are inconsistent, the window is immediately marked as invalid and model file, coefficient, and field validation are performed; when a basic execution cycle ends... Greater than 4.3% or If the concentration exceeds 4.0%, the prescription doses and actual liquid volume of the executed pulses will be included in the cumulative value. The next pulse will be immediately prohibited, and the non-sprayed liquid mixing time of the current cycle will be extended by 60 seconds to a total of 120 seconds. During this period, the feeding or pause status determined by the two moving averages will be maintained. After a new effective window is formed, the next prescription dose that has not yet been executed will be processed. If the original prescription dose was 60 g, it will be forcibly split into two consecutive basic execution cycles of 30 g each. After the first 30 g is executed, the second 30 g will only be allowed to be executed if the cycle end window is valid and the dispersion anomaly is not triggered again. The two 30 g doses will still only complete one 60 g prescription dose, but they will be counted as two execution cycles. If the next prescription dose was originally 30 g, a basic execution cycle of 30 g will be maintained. The splitting must not change the total 0.99 kg quota of S3 and S4. Any further exceedance will require repeating the process of first extending the mixing time, then forming an effective window, and then determining the order of the next pulse. The pulses must not be skipped or executed in parallel. Process validation responds to the false positive rate of a continuous window sequence by moving three consecutive windows. All are between 0.891 and 0.992. None more than 4.3% All are between 0.238 and 0.263 and The condition for a fixed process is defined as a dual-domain window condition where the percentage does not exceed 4.0%. The lower boundary of this quantity corresponds to a false positive probability of 0.7%. If any window fails, the count restarts from the next valid window. The 35-minute control time limit starts independently from the moment the S3 allow feeding signal is received and cannot be paused. The aforementioned start-up sampling phase is included in this time limit. The control system updates the timestamp every 10 seconds and determines the time at the end of each basic execution cycle, extended mixing, and fault recovery according to a unique priority order: First, it checks temperature and oxygen safety, field integrity, and equipment operation. If any of these fail, feeding and spraying are stopped. Then, it checks the remaining time limit, multiplying the number of basic execution cycles required for the unexecuted prescription doses by 90 seconds, and reserving 20 seconds for the three consecutive 10-second update moments after the last pulse. If the earliest completion time will exceed 35 minutes, the next pulse will not be started and isolation will be initiated. Next, it checks that the cumulative dry basis feeding amount does not exceed 34.97 kg and the cumulative adhesive liquid of S3 and S4 does not exceed 0.99 kg. If either upper limit is reached, the corresponding actuator is locked. Finally, it checks the end condition. Only when the cumulative dry basis feeding amount reaches 34.97 kg is the end condition determined. The fixing process ends only when the cumulative adhesive liquid of S3 and S4 reaches exactly 0.99 kg and three consecutive dual-domain windows are simultaneously qualified; if a dual-domain window is qualified first but the feeding amount or adhesive liquid amount is not completed, the process cannot end prematurely. Pausing or resuming feeding is determined only by the next 10-second action command according to the aforementioned dual-domain direction rules. The prescription spraying must still adhere to the remaining quota and cycle sequence. If the cumulative adhesive liquid of S3 and S4 reaches 0.99 kg first but the cumulative dry basis feeding amount has not yet reached 34.97 kg, the spraying valve is locked, and feeding continues only when the current dual-domain window is valid and the feeding action conforms to the target proportion direction; when the cumulative dry basis feeding amount reaches 34.97 kg, the feeder is immediately locked. If there were no previously qualified dual-domain windows, the current window is invalid, the cumulative adhesive liquid amount is not equal to 0.99 kg, or the remaining time limit is insufficient, spraying is immediately stopped and isolation is initiated; if one or two qualified dual-domain windows formed by the most recently updated timestamps are reached when the feeding limit is reached and the cumulative adhesive liquid amount is exactly 0.99 kg, then a maximum of 20 seconds is entered. The endpoint observation is maintained, the feeder and spray valve remain locked, mixing is maintained at 80 r / min, and the forming window sequence is completed according to the predetermined 10 s timestamp. This observation is only used to complete the continuous sequence that has already started and failure windows must not be recounted or fault recovery performed. The fixing process ends when three consecutive double-domain qualified windows are made up within 20 s. If any subsequent window fails, or if there are still not three windows after 20 s or if 35 min expires first, the process is immediately transferred to isolation. Any 60 s additional mixing and 60 g dose splitting caused by any dispersion abnormality consume the 35 min time limit and the same sequence is re-executed after completion. If the three termination conditions are still not met at the end of 35 min, feeding and spraying are immediately stopped and the batch is transferred to isolation. For any quarantine batch, regardless of the cause, a common set of measurement snapshots is established before entering the rework assessment, without directly assuming that existing spectral backtracking results are available: if a set of nine FB samples that have passed the recovery rate and standardized residual thresholds have been available within 10 minutes before the quarantine point, then that set of results is locked; otherwise, only cumulative results are considered. If the value is less than 2, nine samples should be obtained again according to the aforementioned rule of three portions each of the upper, middle, and lower layers, with each portion weighing 10.0 g on a dry basis. Add 1 and record the additional 0.090 kg (dry basis) in the S5 material ledger, accumulating to... If the result is already 2 and there is no valid result within 10 minutes, rework is not allowed. For the nine locked samples, the ratio of iron from two sources is obtained using multi-receiver ICP-MS and the S1 binary solution matrix. The current total iron mass is obtained by multiplying the average total iron mass fraction of the nine samples measured by ICP-OES by the dry basis mass of the master batch at the isolation time. This is then allocated according to the binary solution ratio to the current iron mass from ferrous fumarate and iron from sodium EDTA. Additionally, three 2.0 g samples are taken from the composite sample formed by combining equal masses of the nine samples and measured to constant weight to obtain the average drying weight loss at the isolation time. This average, along with the actual particle temperature, nitrogen flow rate, and bed pressure difference, is input into the DR-04 drying prediction table. This table is established by combining three batches of verified particles at a drying weight loss of 2.0% to 12.0%, a particle temperature of 28℃ to 32℃, and a nitrogen flow rate of 18 m³ / h to 25 m³ / h. The table provides 45% linear interpolation between adjacent levels. The predicted loss on drying must be accurate, with an independent verification absolute prediction error not exceeding 0.20 percentage points. Rework is prohibited if the input exceeds the table range or the prediction error threshold is not met. Rework assessment for isolated batches is based on the following data: current iron content from both sources, remaining amount of post-processed dry powder premix, remaining amount of 0.99 kg binder formulation quota, cumulative feed amount, simultaneous moisture content and dry basis weight of each material, and all other relevant data. Domain and Domain movement window, DR-04 pre-drying weight loss prediction value, and S2 wet phase oxygen exposure index; only when the current ratio of iron from sodium ferric ethylenediaminetetraacetate to iron from ferrous fumarate is less than 0.238, the near-line ferrous retention rate is not less than 97.0%, the predicted drying weight loss can reach the S5 physical endpoint, and the required replenishment amount is positive and does not exceed the remaining dry basis feed margin, will one-time rework be initiated. If the current ratio is higher than 0.263, any precondition is not met, or there is no remaining binder formula quota, isolation must be maintained and no correction by adding ferrous fumarate or other raw materials is allowed; the rework target ratio is fixed at 0.250. First, multiply 0.250 by the current ferrous fumarate source iron mass and then subtract the current ethylenediaminetetraacetate source iron mass. The resulting positive difference is the ethylenediaminetetraacetate source iron mass to be replenished, and then divided by the ethylenediaminetetraacetate source iron mass contributed per kg of dry basis by the S1 post-dry powder premix, which is 0.05713. The unique dry basis feed rate of 0.05713 kg / kg is obtained by multiplying the dry basis mass fraction of sodium iron EDTA (43.12%) by its release measured iron mass fraction of 13.25%. The calculated feed rate must not exceed the remaining post-processed dry powder premix, nor should the cumulative dry basis feed rate exceed 34.97 kg. Upon approval, a controlled feed rate of 0.30 kg / min is performed once at an oxygen volume fraction not exceeding 0.60%, using only the unused binder from the 0.99 kg prescription quota according to the current 90 s cycle execution table. The amount used must not exceed the remaining quota. After the feed rate is completed, maintain a no-spray mixing speed of 80 r / min for 120 s. After rework begins, continuously obtain 30 valid spectra and recalculate simultaneously. , , and Only when three consecutive moving windows meet the requirements The value ranges from 0.891 to 0.992. No more than 4.3% The value ranged from 0.238 to 0.263 and The isolation period is lifted only when the mass recovery rate of input, sample, residue and main particles is between 99.95% and 100.05% after unified dry basis verification, and the rework starts independently from the first feeding and is limited to a maximum of 10 minutes. Only one rework is allowed per batch. If any window fails during the period, the count will be restarted but the time limit will not be extended. If the dual-domain window and dry basis quality conditions are not met at the end of the period, the feeding or adhesive liquid is insufficient, the equipment operation exceeds the limit or the ferrous iron retention rate is not qualified, feeding and spraying will be stopped immediately and the isolation final state will be maintained. No second rework will be carried out. To maintain the sample spectrum of space and discharge time, after fixation, the equipment was divided into front, middle and rear sections according to the cumulative discharge amount of 0% to 10%, 45% to 55% and 90% to 100%. 100 g of particles were taken from each discharge section through three sealed sampling ports on the upper, middle and lower layers of the equipment to form nine samples with unique space-time identifiers. Each sample was placed in a gas-permeable stainless steel mesh sample box with the same RFID tag. The main particles from the three discharge sections entered nitrogen-protected transfer containers, and the container tags recorded the time period and the three space sample identifiers. The nine sample boxes and the three main particle containers were transferred to S5 through a sealed docking. The source identifier list was retained for any container merging. Online near-infrared spectroscopy is only used for process control in the ratio and conversion domains, and its average spectrum is not used to infer the radial layer of particles. The layer is confirmed by a spatial resolution verification chain. In this batch, one complete representative particle was taken from each of the nine space-time sample boxes. After low-temperature resin embedding and cross-sectional preparation, confocal micro Raman 2D mapping with a pixel resolution of no more than 5 μm was performed. Peak crosstalk was corrected with pure ferrous fumarate and pure sodium ferric ethylenediaminetetraacetate calibration samples. The normalized radius from the particle centroid to the edge of 0.70 to 1.00 was defined as the outer layer. In the nine cross-sections, at least 80% of the integrated signal of the ethylenediaminetetraacetate coordination marker peak after background subtraction was located in the outer layer. At the same time, the fumarate marker peak penetrated the central region. Therefore, after confirmation by this spatial resolution result rather than online average spectrum, the iron source was fixed to the outer layer of the ferrous fumarate core. The calibration sample, original mapping map and cross-section identification were archived with the main batch number. Upon receiving the S3 permission signal, this batch completed a self-test of the probe and actuator with zero feeding and zero spraying, and then entered the start-up sampling phase with a 35-minute time limit. Within the first 5 minutes, a fixed feeding rate of 1.20 kg / min and pre-approved dosage were used, obtaining 30 valid spectra before transitioning to a dual-domain closed-loop system. The feeding volume, spraying volume, and time during the start-up phase are all included in the following cumulative values. The feeding setting of the loss-in-weight feeder in this batch was 1.20 kg / min. The cumulative feeding time was 29.14 minutes, and the cumulative feedback pause time was 1.86 minutes. At the 30-minute 40-second update timestamp, the cumulative feeding reached 34.97 kg, simultaneously forming the first dual-domain qualified window, and the control system immediately locked the feeder. The pulsed liquid supply branch executed 20 non-overlapping 90-second complete cycles sequentially in the first 30 minutes, spraying 60 g of liquid in each of the first 13 cycles and 30 g of liquid in each of the last 7 cycles, according to the pre-approved quota execution table. g, neither of the two relative standard deviations in this batch triggered the extended mixing abnormal branch. A total of 0.99 kg of the same batch of deoxidized adhesive was used, and 0.0396 kg of povidone dry solids were introduced, exactly reaching the S1 pre-approved prescription quota. The remaining 0.01 kg of the pipeline at the end of the branch was weighed and sealed after completion and did not enter the product. No more liquid was sprayed from 30.00 to 31.00 min. At 30 min 40 s, when the upper limit of feeding was reached, there was already a dual-domain qualified window and the cumulative amount of adhesive was 0.99 kg. Therefore, according to the endpoint observation and maintenance rules, the feeder and spray valve were locked, and mixing was maintained at 80 r / min for 20 s. The second and third windows were completed sequentially at 30 min 50 s and 31 min 00 s, respectively, and the process ended. The three consecutive moving windows corresponding to the control times of 30 min 40 s, 30 min 50 s, and 31 min 00 s yielded... The values ​​are 0.927, 0.939, and 0.947. The corresponding figures are 3.0%, 2.6%, and 2.3%. The values ​​are 0.247, 0.250, and 0.252. The percentages were 2.8%, 2.4%, and 2.1%, respectively. All dual-domain statistics met the termination criteria. No continuous liquid film was observed in the near-infrared images of the particles. The median particle size of the discharged composite particles was 510 μm. The control system transmitted the three main particle containers, nine space-time sample boxes, cumulative feed amount, number of S4 adhesive pulses, actual usage, remaining amount, povidone dry solids, SP-05 model version, and all window statistics to S5.

[0023] In this specific embodiment, S5 includes: In this specific embodiment, the three nitrogen-protected main particle containers obtained in S4 are sequentially transferred into an independent low-temperature, low-oxygen drying device through a sealed connection. Nine mesh sample boxes are fixed on the sample racks at the corresponding heights of the drying device according to their upper, middle, and lower layer markings, so that the particles in the sample boxes and the main particles experience the same atmosphere and temperature process. The nitrogen flow rate is set to 20 m3 / h, the inlet air temperature is set to 35°C, and the particle temperature is kept below 32°C through jacket cooling. The oxygen volume fraction of the device is kept below 1.0%. The inlet air temperature, particle temperature, oxygen volume fraction, exhaust dew point, and bed pressure difference are recorded every 5 minutes. If the temperature or oxygen volume fraction exceeds the limit, the heating power is immediately reduced and the nitrogen flow rate is increased. If the temperature or oxygen volume fraction cannot be restored after 2 minutes, the drying heating is stopped and the batch is transferred to an isolation state. Loss on drying was measured at five time points: 10, 20, 30, 40, and 45 min, using parallel samplers taken from a nitrogen-protected sampling port. Before sampling, the required wet basis sample size for each sample to reach a nominal dry basis of 2.0 g was estimated using synchronous near-infrared moisture values ​​that had been calibrated offline for constant weight and independently verified with an absolute error not exceeding 0.20 percentage points. This estimated value was only used to set the sample size and was not used as the actual loss on drying result. The corresponding actual wet basis weight was recorded as follows: The mass obtained by measuring to constant weight at 105℃ is recorded as follows. Ten samples were measured at five different times and then not resampled; each sample was tested individually. As a record of material loss, the total actual constant weight dry basis mass of the ten portions in this batch is 0.020 kg; loss on drying is calculated as follows: calculate, Indicates time Loss on drying of the sample, in % The dimensionless positive integer indices representing the sampling times during the drying process correspond to 10, 20, 30, 40, and 45 min, respectively. This indicates the actual wet basis mass of the sample before constant weight, in grams. This represents the constant weight dry basis mass of the same sample, in grams, and is the recorded value of material loss for this transaction. The denominator is... The difference between two parallel results at the same time exceeds 0.20 percentage points. If the difference is still too large, the data at that time should be marked as invalid and kept dry. The actual constant weight dry basis mass of the resampled sample will be included in the batch loss separately. Water activity was measured using a constant-temperature water activity meter at 25.0±0.2℃. The instrument was calibrated daily with standard salt solutions at two points, 0.250 and 0.760. Two samples were taken at each of the five sampling times mentioned above. For each sample, the wet basis sample weight required to achieve a nominal dry basis of 5.0 g was estimated based on the calibrated synchronous near-infrared water activity value at that time. The actual wet basis weight and the measured wet basis weight were determined according to the synchronous measurement. The actual dry basis mass was recorded for each sample. The total actual dry basis mass of the ten samples at five different times in this batch was 0.050 kg, and the samples were not re-tested after measurement. The readings were balanced until the change within 5 minutes did not exceed 0.003. The stability test and dissolution consistency test set the loss on drying not exceeding 3.0% and the water activity not exceeding 0.35 as two physical endpoints. Physical drying was only terminated when both parallel samples at the same sampling time reached the corresponding limits. If any physical endpoint was not reached at 45 minutes or the data at that time was invalid, the loss on drying and water activity were remeasured simultaneously every 5 minutes at 50, 55 and 60 minutes under the same temperature and oxygen limit. For each new time point, the wet basis sampling amount of each type of sample was estimated using the synchronous near-infrared moisture value calibrated at the same time, and the actual constant weight dry basis mass or the same time period was used. The converted actual dry basis mass is included in the material verification. The nominal dry basis target totals 14.0g and is not recycled. The upper limit of the actual dry basis total when all three uses are completed is 0.042 kg. If two physical endpoints are reached at any new time, the process will switch to the chemical endpoint. If the data from two consecutive sampling times are invalid, the total drying time reaches 60 min but the two physical endpoints are not reached, or the temperature and oxygen safety conditions cannot be maintained, heating will be stopped immediately, nitrogen and low-speed mixing will be maintained, and the batch will be transferred to the isolation final state. Drying will not be extended indefinitely. After both physical endpoints reached their corresponding release limits, the near-line ferrous content of the particle samples was determined. Near-line samples were composed of samples from nine types of space-time samples in a specific mass ratio. After acidification and deoxygenation dissolution, the ferrous content was determined by cerium titration, and the total iron content was verified by ICP-OES. The ferrous retention rate was calculated according to... calculate, This indicates the ferrous iron retention rate after physical drying, expressed in %. This represents the measured ferrous mass calculated from the near-line ferrous content, in kg. The amount of ferrous fumarate contained in the feed is expressed in kg. The chemical endpoint release limit is determined to be no less than 95.0% for stability and dissolution verification. When the ferrous iron retention rate reaches 95.0%, the chemical endpoint is confirmed and drying is stopped. If it is below 95.0%, the batch is immediately transferred to isolation and the chemical endpoint determination cannot be replaced by extending the drying process. The isolation investigation verifies the S2 wet phase oxygen exposure index, S3 surface dry switching record, S4 feeding window and S5 temperature-oxygen curve. The test results are updated only when the test method deviation is confirmed and the sample retest meets the pre-approved retest procedure. Batches with low ferrous iron retention rate due to process reasons are not reworked. The preset drying temperature limit, drying oxygen limit, and three endpoint limits were determined by drying three batches of process validation particles at particle temperatures of 28, 30, 32, and 35°C and oxygen volume fractions of 0.5%, 1.0%, 1.5%, and 2.0%, and then observing their stability for 0, 1, 3, and 6 months, as well as by a leaching consistency test in the specified medium. The boundary selection was based on the most unfavorable condition that simultaneously met the following requirements: ferrous iron retention rate of not less than 95.0%, overall color difference of not more than 3.0%, and relative standard deviation of leaching amount of not more than 10.0%. The validation report number, sample batch number, and limit version DR-04 were written into the batch record. To ensure each sample's identifier remained with its corresponding composite particle until the same batch of drying was completed, the unique identifier of each of the nine mesh sample boxes was maintained with its corresponding composite particle within the box. After reaching the physical and chemical endpoints, each box was removed and samples were prepared according to their original identifiers. Multi-detector ICP-MS was used to determine the 57Fe / 56Fe and 58Fe / 56Fe ratios of each sample. Using the measured isotopic fingerprints of the two release raw materials (S1) and a binary solution matrix locked by seven known mixing ratio standards, the iron mass from the ferrous fumarate raw material and the iron mass from the sodium iron ethylenediaminetetraacetate raw material in each sample were directly inverted. This source attribution is determined only by stable isotopic fingerprints and therefore does not change due to coordination exchange or valence state changes during drying. HPLC-ICP-MS was used to determine the coordinated iron in ethylenediaminetetraacetate, and ICP-OES was used to determine the total iron. This set of results only verified the coordination form and total amount, and the difference between total iron and coordinated iron was not used to replace the source iron mass. Content assignment controls were used for each method. For standard, blank, and spiked recovery samples, the recovery rate of a single sample must be between 97.0% and 103.0%, and the standardized residual of the binary isotope solution must not exceed 2.0%. The proportion uniformity limit is derived from the unit dose iron content uniformity verification under No. UD-04. In three batches of process verification, nine space-time samples from each batch were prepared into ten unit doses, resulting in a total of 270 unit doses. The iron proportions from the two sources obtained by stable isotope inversion, the total iron content of ICP-OES, and the unit dose were recorded simultaneously. Dose Acceptance Values; When the relative standard deviation of the iron content from the source at position nine does not exceed 5.0%, the elemental iron content of 270 unit doses is all between 90.0% and 110.0% of the labeled amount, and the acceptance value of each batch does not exceed 15.0%. The upper confidence limit of the 95% relative standard deviation of the iron content from the source is 4.72%. Based on this, 5.0% is rounded up and determined as the release limit for the uniformity of the finished product ratio. For the same UD-04 data, 80% of the finished product release limit, i.e., 4.0%, is set as the S4 conversion domain. The internal process control limits are used, and the S4 ratio range is obtained by combining the SP-05 calibration error propagation. The content should not exceed 4.3%. Therefore, 4.0% and 4.3% of S4 are used for advance control and are stricter than or serve the 5.0% finished product release limit of S5. Passing S4 does not replace independent testing of S5, and passing S5 does not cover S4 process abnormalities. The relative standard deviation is calculated by the ratio of iron from sodium EDTA to iron from ferrous fumarate obtained from the inversion of nine samples and compared with the 5.0% ratio uniformity limit. If the coordinated iron is higher than the total iron, the isotope solution residual exceeds the limit, or the recovery rate is unqualified, the sample result is invalid and it is re-prepared according to the original box label. If the retest is still abnormal, the whole batch is isolated. Color difference testing employed the comprehensive color difference value under the same illumination conditions, specifically using the CIELAB 1976 color space. Nine samples were measured under a standard daylight illuminator (D 65°), a 10° standard observer, and the same white sample cup. Each sample was rotated 120° and measured three times, with the coordinates averaged. The controlled reference was a CR-04 comprehensive color difference reference board, jointly established and sealed and stored from three batches of process-validated batches. Its assigned coordinates under the same conditions were 72.4, 8.1, and 18.6. Before and after use, a white board was used for verification; any coordinate shift exceeding 0.20 was invalid for this test. The comprehensive color difference was calculated as follows: calculate, This represents the dimensionless CIELAB 1976 composite color difference of the sample relative to the CR-04 reference plate. , and The coordinates of the dimensionless lightness, red-green axis, and yellow-blue axis, respectively, are the average of three measurements of the sample. , and The dimensionless lightness, red-green axis, and yellow-blue axis coordinates of the CR-04 reference plate are represented sequentially, and are 72.4, 8.1, and 18.6 respectively for this batch; the same reference system was established in three batches of process validation. A color difference of no more than 3.0 is used as a release condition for color difference; for dissolution testing, 12 sampling units are randomly selected from the finished products with equal mass composition of nine types of samples. The samples are taken for 30 min in 900 mL of pH 1.2 hydrochloric acid medium, 37.0±0.5℃ and 50 r / min paddle method. The amount of elemental iron dissolved is determined by ICP-OES, and the relative standard deviation of the 12 dissolution amounts not exceeding 10.0% is used as a release condition determined by dissolution consistency verification. If any result of uniformity, color difference or dissolution consistency is unqualified, the quality system will locate the source of the anomaly according to the original spatial-temporal sample identification and isolate the entire batch. The qualified result of the unidentified mixed sample will not cover the positional anomaly. Only when the suitability of the testing system or the sample preparation deviation is confirmed in writing will the test be retested according to the preset procedure. The batch that fails the process will not change the original judgment by remixing, adding drying or adding any iron source. This batch achieved a drying loss of 2.42% and a water activity of 0.29 after 45 minutes of drying, therefore the 50-60 minute extended drying period was not activated. The peak particle temperature was 31.2℃, the peak oxygen volume fraction was 0.83%, and the near-line ferrous phosphate retention rate was 97.3%. This batch did not trigger S3 rehumidification or S4 immediate reversal. and All are 0; the dry basis material verification uniformly uses the conversion relationship of S1, starting from an initial dry basis total of 100.50 kg, consisting of two iron sources, carrier, conditioning components, 0.184 kg of povidone contained in 4.60 kg of binder in S2, and 0.0396 kg of povidone contained in 0.99 kg of pre-approved formulation quota in S3 and S4. The actual wet basis weighing value of each material is based on its own measured value. After conversion, the amount is recorded; deducting the actual wet basis weighing value and the synchronous value. The converted dry basis weights are: S1 ten-point sample 0.20 kg, S2 two-times pH sample 0.02 kg, S2 ten-times particle size sample 0.20 kg, S5 loss on drying sample confirmed by constant weight 0.020 kg, and the same period... The converted water activity sample dry basis is 0.050 kg, and the wet basis weighed after equipment cleaning and converted using synchronous moisture content is 0.010 kg. The total dry basis loss during the routine process is 0.500 kg, resulting in a batch dry basis mass of 100.00 kg before destructive release inspection without triggering immediate retraction. If S4 triggers immediate retraction, an additional 0.090 kg will be deducted. kg and the adjusted target dry basis mass is The sum of the measured dry basis masses of the three main particle containers and nine sample boxes must be between 99.95% and 100.05% of the adjustment target; otherwise, isolation is required. If an extended branch is enabled, the measured or converted dry basis mass at each new sampling time will be deducted, with a maximum deduction of 0.014 kg per time. There is no immediate rollback or extended branch deduction for this batch. The final particle synchronous moisture content... The actual wet basis weight of the three main particle containers is 101.5577 kg, which is converted to 99.10 kg on a dry basis according to the S1 relationship. The actual wet basis weight of the nine space-time sample boxes is 0.9223 kg, which is converted to 0.90 kg on a dry basis. The two together constitute the aforementioned dry basis weight of 100.00 kg. kg; the subsequent layering and release inspection consumption of the nine sample boxes are listed separately as the destination of the released samples and are not repeatedly included in the aforementioned process losses; the average content ratio of the two iron sources in the nine sample boxes obtained by stable isotope fingerprinting is 0.249, the relative standard deviation is 3.1%, the maximum comprehensive color difference is 1.84, and the relative standard deviation of the elemental iron dissolution of 12 sampling units over 30 minutes is 5.7%. All of them meet the physical endpoint, chemical endpoint and quality release conditions specified in DR-04. Finally, the batch number of the composite iron agent, the spectrum of the nine types of samples, the temperature and oxygen data throughout the process, the ratio of the two iron sources, the color difference and dissolution results are archived and a composite iron agent product is formed. Thus, the same batch implementation verification of a method for preparing a composite iron agent of ferrous fumarate and EDTA iron sodium is completed.

[0024] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

[0025] This invention organically combines wet-phase oxygen exposure index, surface-dry switching determination, feedback of the spectral characteristics of the two iron sources, and determination of dual physical and chemical endpoints during the drying process, forming a closed-loop control chain covering "nucleation-layering-fixation-drying-release". This combination is not a simple adjustment of a single process parameter, but rather addresses the technical problems of easy oxidation of ferrous fumarate, easy migration of iron and sodium EDTA, and uneven distribution of the two iron sources within the particles by setting oxygen exposure constraints, liquid film state determination, ratio uniformity feedback, and ferrous retention rate constraints. This allows the two iron sources to sequentially enter the same composite particle under a controlled low-oxygen environment and stably fix at different layers, thereby reducing oxidation loss, reducing migration and enrichment, improving color consistency and uniformity of iron content per unit dose, and improving storage stability and dissolution consistency.

[0026] This invention incorporates structural improvements oriented towards process conditions: First, it introduces the continuous liquid film state on the particle surface into the surface dryness switching determination, ensuring that the addition of the subsequent iron source is within a process window that is "depositable but not easily migrated"; Second, it constructs a wet-phase oxygen exposure index by linking oxygen volume fraction, particle moisture content, and temperature, and sets graded interlocking thresholds to achieve dynamic suppression of oxidation risk; Third, it utilizes the spectral characteristic ratio of the two iron sources and a continuously moving window for feedback adjustment, enabling the feed rate, spraying cycle, and mixing time to adaptively correct according to the spatial distribution of the particles; Fourth, it uses drying weight loss, water activity, and ferrous iron retention rate together to determine the endpoint, avoiding the defect of only achieving physical drying while ignoring chemical stability. These structural improvements enable the various control links to cooperate and constrain each other step by step, which is more conducive to achieving the technical effects described in this invention.

Claims

1. A method for preparing a composite iron agent of ferrous fumarate and EDTA iron sodium, characterized in that, include: S1. Determine the amount of ferrous fumarate and sodium ferric ethylenediaminetetraacetate according to the target element iron ratio. Mix sodium ferric ethylenediaminetetraacetate with the first carrier to obtain the post-dry powder premix. Use ferrous fumarate and the second carrier as the pre-feed components. S2. After inerting in the granulation equipment, the pre-feed components are granulated by segmented spraying with deoxygenated binder to obtain ferrous fumarate cores. S3. Determine the surface dry switching point where the continuous liquid film on the surface of the ferrous fumarate nucleus disappears but still has residual adhesion. S4. After the surface drying switching point, add the post-dry powder premix and use deoxygenated adhesive liquid for pulse spraying and mixing to fix sodium iron ethylenediaminetetraacetate on the outer layer of the ferrous fumarate core, so as to obtain composite particles with two iron sources in the same particle. S5. Dry the composite particles within the preset drying temperature limit and drying oxygen limit to obtain the composite iron agent finished product.

2. The method for preparing the ferrous fumarate and EDTA iron-sodium composite iron agent according to claim 1, characterized in that, S1 includes: The elemental iron content of ferrous fumarate and sodium iron ethylenediaminetetraacetate raw materials were determined separately, and the theoretical feed mass was corrected by their respective elemental iron content. The first carrier is selected from at least one of microcrystalline cellulose, pregelatinized starch, maltodextrin and mannitol, and the relative standard deviation of the sodium iron ethylenediaminetetraacetate content of the post-dry powder premix, as measured by multi-point sampling, is within the premix uniformity limit. The target element iron ratio and premixing uniformity limits are determined by the product formulation and process validation results.

3. The method for preparing the composite iron agent of ferrous fumarate and EDTA iron sodium according to claim 1, characterized in that, S2 include: The deoxygenated adhesive is prepared with deoxygenated water, and inert gas protection is maintained during the preparation, transportation and spraying process. According to the fixed solid-liquid mass ratio determined by process verification, a representative sample of the pre-feeding component is mixed with a specified amount of water to form a dispersion. The pH of the dispersion is measured at a fixed measurement temperature and a fixed settling time. The amount of microenvironment pH adjusting component is determined based on the measured pH. The microenvironment pH adjusting component is added to the pre-feeding component so that the measured pH of the pre-feeding component after adding the microenvironment pH adjusting component enters the stable range determined by the ferrous ferrous fumarate retention rate test. The granulation equipment is inertized until the oxygen volume fraction is within the preset oxygen limit, and the particle temperature is maintained within the preset granulation temperature limit during the segmented liquid spraying granulation process. The preset oxygen limit and preset granulation temperature limit are determined by the boundaries of the ferrous iron retention rate meeting the corresponding release limit in the oxygen volume fraction gradient test and particle temperature gradient test, respectively.

4. The method for preparing the ferrous fumarate and EDTA iron-sodium composite iron agent according to claim 3, characterized in that, In step S2, the wet phase oxygen exposure index is obtained, wherein obtaining the wet phase oxygen exposure index includes: By using calibration particles with and without continuous liquid films on their surfaces, a correspondence between near-infrared moisture signals and liquid film states is established, and the boundary value between the two liquid film states is determined as the critical value of the continuous liquid film. The measured oxygen volume fraction before the pre-feeding components are added after inerting by the granulation equipment is used as the inerting reference value, and the inerting reference value is within the preset oxygen limit value; Synchronous data sets of oxygen volume fraction, near-infrared particle moisture, and particle temperature are formed according to sampling time intervals. When the near-infrared particle moisture is within the critical value of the continuous liquid film, the wet phase oxygen exposure contribution of the corresponding sampling time interval is recorded as zero. When the near-infrared particle moisture exceeds the critical value of the continuous liquid film, the wet phase oxygen exposure contribution is determined according to the deviation of the oxygen volume fraction from the inertization reference value, the oxidation rate correction coefficient corresponding to the particle temperature, and the sampling time interval, and the wet phase oxygen exposure contributions are accumulated.

5. The method for preparing the composite iron agent of ferrous fumarate and EDTA iron sodium according to claim 1, characterized in that, S3 include: The calibration time when the continuous liquid film on the surface disappears is determined by particle surface imaging, and the calibration period when the residual adhesion is qualified is determined by the adhesion ratio of standard probe powder after a specified mixing time. The calibration time and calibration period are respectively correlated with the change trajectory of at least one of near-infrared particle moisture, torque and power, and exhaust absolute moisture content to establish a surface dryness determination interval with entry and exit boundaries. When the near-infrared particulate moisture enters the surface drying determination range, the rate of change of torque or power enters the stable zone, and the absolute moisture content of the exhaust air no longer increases within the determination time window, the surface drying switching point is determined to have been reached. When the near-infrared particle moisture has not yet reached the entry boundary along the moisture descent direction, mixing and inertization are maintained. When the near-infrared particle moisture crosses the exit boundary or when the criteria are not simultaneously met by the time the preset waiting period expires, subsequent layering is stopped and the corresponding batch is transferred to the isolation state. Batches that meet the verified rework conditions are reworked according to the safety threshold of low oxygen and ferrous iron retention rate.

6. The method for preparing the composite iron agent of ferrous fumarate and EDTA iron sodium according to claim 1, characterized in that, S4 include: The spectra of ferrous fumarate and sodium ferric ethylenediaminetetraacetate were collected respectively to determine the first characteristic band of the response to fumarate and the second characteristic band of the response to the coordination structure of ethylenediaminetetraacetate. After scattering correction and baseline correction of the spectrum of the composite particles, the spectral feature scores are obtained based on the response values ​​of the first and second characteristic bands, respectively. The ratio of the spectral feature scores is determined by using the spectral feature score corresponding to the second feature band as the numerator and the spectral feature score corresponding to the first feature band as the denominator. The elemental iron ratio is determined by using the elemental iron content from sodium iron ethylenediaminetetraacetate as the numerator and the elemental iron content from ferrous fumarate as the denominator. Based on calibration particles with known iron ratios of two iron source elements, a correspondence is established between the ratio of spectral feature scores and the elemental iron ratio. The moving mean and relative standard deviation of the ratio of spectral feature scores are calculated within a continuously moving window. The allowable range corresponding to the target elemental iron ratio is taken as the target ratio range, and the maximum allowable relative standard deviation for unit dose iron content uniformity verification is taken as the spatial uniformity limit.

7. The method for preparing the ferrous fumarate and EDTA iron-sodium composite iron agent according to claim 4, characterized in that, Set a first interlock threshold, a second interlock threshold, and a preset exposure limit, and set the first interlock threshold, the second interlock threshold, and the preset exposure limit in a sequentially increasing numerical relationship; When the wet phase oxygen exposure index reaches the first interlocking threshold, the spray duty cycle of the deoxygenated adhesive is reduced and the inert gas replacement flow rate is increased. When the wet phase oxygen exposure index reaches the second interlock threshold, the spraying is stopped and mixing and inerting are maintained to prevent the cumulative value of the wet phase oxygen exposure index from falling back until the oxygen volume fraction in the equipment is within the reset oxygen limit and the near-infrared particle moisture is within the critical value of the continuous liquid film. Then the surface dry switching determination in step S3 is resumed. When the wet phase oxygen exposure index reaches the preset exposure limit, the corresponding batch will be transferred to isolation status; The first interlock threshold, the second interlock threshold, the reset oxygen limit, and the preset exposure limit are determined by the batch verification relationship between the wet phase oxygen exposure index and the ferrous iron retention rate. The reset oxygen limit is within the preset oxygen limit, and the ferrous iron retention rate corresponding to the second interlock threshold meets the ferrous iron retention rate release limit.

8. The method for preparing the ferrous fumarate and EDTA iron-sodium composite iron agent according to claim 6, characterized in that, During the fixation process of sodium iron ethylenediaminetetraacetate, the moving mean and relative standard deviation are updated according to a continuously moving window. When the moving average is less than the lower limit of the target ratio range, increase the feed rate of the post-dry powder premix per unit time; when the moving average is greater than the upper limit of the target ratio range or the moving average is within the target ratio range, stop feeding. When the relative standard deviation is greater than the spatial uniformity limit, while maintaining the feeding state determined by the moving average, the mixing time is extended and the amount of liquid injected in a single pulse is reduced. The fixation process of sodium ferric ethylenediaminetetraacetate ends only after the moving mean and relative standard deviation of multiple consecutive moving windows are both qualified. The number of consecutive moving windows is determined by the lower boundary of the number of windows whose misjudgment probability does not exceed the preset misjudgment limit in the process verification. Divide the amount of sodium ferric ethylenediaminetetraacetate (EDTA) determined in step S1 by the measured mass fraction of EDTA in the subsequent dry powder premix, and combine it with the allowable deviation determined by process verification to obtain the total feed limit of the subsequent dry powder premix. When the cumulative feeding amount reaches the total feeding limit or the preset control time limit expires and the moving average or relative standard deviation is still unqualified, feeding and spraying are stopped and the corresponding batch is transferred to the isolation state. Batches that meet the verified rework conditions are reworked according to the target element iron ratio, drying loss and ferrous iron retention rate safety threshold.

9. The method for preparing the composite iron agent of ferrous fumarate and EDTA iron sodium according to claim 8, characterized in that, S5 include: During the drying process, the weight loss on drying and water activity are simultaneously acquired. The weight loss on drying and water activity reaching their respective release limits are taken as two physical endpoints. If either physical endpoint fails to reach its corresponding release limit, drying continues. After both physical endpoints reach the corresponding release limits, the near-line ferrous content of the particle sample is determined, and the ferrous retention rate is determined by the ratio of the near-line ferrous content to the ferrous content of ferrous fumarate at the time of feeding. The ferrous retention rate reaching the corresponding release limit is taken as the chemical endpoint. When the ferrous iron retention rate does not reach the corresponding release limit, the corresponding batch will be transferred to the isolation state instead of using extended drying to replace the chemical endpoint determination. The preset drying temperature limit, drying oxygen limit, and release limits for drying loss, water activity, and ferrous iron retention are determined jointly by stability tests and dissolution consistency tests.

10. The method for preparing the ferrous fumarate and EDTA iron-sodium composite iron agent according to claim 9, characterized in that, Establish sample labels at different spatial locations and discharge time periods in the granulation equipment, and keep each sample label with the corresponding composite granules until the same batch is dried; The test for the uniformity of the two iron sources includes taking samples from the same batch of composite particles that have reached the physical and chemical endpoints according to the sample identification, determining the content ratio of iron from ferrous fumarate and iron from sodium ferric ethylenediaminetetraacetate in each sample, and taking the relative standard deviation of the content ratio as being within the ratio uniformity limit determined by the unit dose iron content verification as the release condition for ratio uniformity. Color difference inspection uses the comprehensive color difference value under the same lighting conditions, and the condition for color difference release is that the comprehensive color difference value is within the color difference limit established by the qualified batch of process verification. The dissolution test measures the amount of elemental iron dissolved from multiple sampling units in a specified medium and at a specified sampling time. The release condition is that the relative standard deviation of each dissolution amount is within the limit determined by the dissolution consistency verification.